출산 후 엘리트 선수의 임신 전 훈련으로의 복귀 시점: 체계적 문헌고찰 및 메타분석 - 박영민; 강년주; 홍광석; 조진경; 한태경; 박수현 (Exercise science (Seoul, Korea), 2024)
PURPOSE: Female athletes often face challenges in returning to exercise training programs after pregnancy and parturition. This study aimed to conduct a meta-analysis to investigate the optimal duration for elite female athletes to resume their pre-pregnancy training programs. METHODS: Nine studies were included in this meta-analysis with a total of 1,466 women, comprising 567 nonathletes and 899 athletes. The effect sizes were calculated as differences in health-related indicators, athletic performance, and training volume during five periods: early, mid, and late pregnancy; within 6 months postpartum; and between 7 and 12 months postpartum, compared with prepregnancy levels. RESULTS: Female athletes included in the study did not return to their pre-pregnancy physical condition even one year postpartum. Health indicators decreased substantially during pregnancy and remained lower than pre-pregnancy levels for up to one year postpartum. During pregnancy, there was a considerable reduction in training volume, which persisted throughout one year postpartum. However, athletic performance within the first year postpartum was not significantly different from pre-pregnancy levels; this finding is based on a single study, indicating a limitation due to the insufficient number of studies included in the analysis. CONCLUSIONS: This study demonstrated that female athletes did not fully recover their physical condition or function within one year postpartum. Nevertheless, this finding does not imply that female athletes are unprepared or unable to resume exercise training within one year postpartum. Sufficient return to training can be achieved within this timeframe, but it is crucial to progressively and safely increase training volume and intensity in accordance with individual physiological recoveries KCI Citation Count: 0